Physical Vulnerability Index before the Landsliding Hazard in Houses Located in the Locality of Rafael Uribe Uribe, Bogotá D.C. - Acosta Jiménez, Yamith; Peña Rincón, Carlos Arturo (TECCIENCIA, 2020)
The present work carried out an analysis study of the physical vulnerability index for the hazard of landslide for the Rafael Uribe Uribe locality in Bogotá DC, using the Leona methodology with historical data of mass removal between the years 2008 to 2015, with a registry of 454 events, of which 426 are considered, given that the rest corresponds to rock falls, which may also affect general vulnerability, the methodology used does not apply. Technical concepts have been designed for the competent entities in the sectors that have presented the phenomenon of the mass removal in Rafael Uribe Uribe and the existing technical sheets for each of them, as well as the delimitation of each of the polygons, was carried out on a local map with 31 polygons that historically have presented a phenomenon of mass removal. The physical vulnerability index of the elements exposed to the situation of the events that can be classified as deformations or lateral displacements, which can be classified as moderate, is adjusted, however, the periods of rain, the solicitations may present deformations very fast.